Improved Decisional Conflict and Preparedness for Decision Making Using a Patient Decision Aid for Treatment Selection in Psoriasis: A Pilot Study. Issue 2 (March 2014) - Tan, Jerry; Wolfe, Barat
Background: We developed a patient decision aid (pDA) to assist psoriasis patients in treatment decisions. Objective: This pilot study evaluated the pDA in patient knowledge, decisional conflict, and preparation for decision making. Methods: Newly referred psoriasis patients in a private dermatology office completed self-administered surveys at three time points: before (visit 1) and on two occasions after provision of the pDA (visit 2 up to 2 weeks after visit 1; visit 3 up to 6 weeks after visit 1). The survey included questions regarding knowledge of psoriasis and its treatment and validated questionnaires on decisional conflict and preparation for decision making. Results: Ten psoriasis patients participated (seven men, three women; mean age 45.7 years), with a mean age of 11.4 years since diagnosis. Improvement by visit 3 was observed for knowledge ( p = .06), reduced decisional conflict ( p ≤ .001), and preparation for decision making ( p ≤ .05). Patients tended to self-select treatment appropriate to the level of psoriasis severity. Conclusion: This pilot study of the pDA showed improved patient knowledge of psoriasis and its treatments, reduced decisional conflict, and increased patient preparation for decision making. Limitations: This small study was not randomized and did not have a comparator arm.